Advances in Flexible Metallic Transparent Electrodes. Issue 19 (23rd February 2022) - Nguyen, Viet Huong; Papanastasiou, Dorina T.; Resende, Joao; Bardet, Laetitia; Sannicolo, Thomas; Jiménez, Carmen; Muñoz‐Rojas, David; Nguyen, Ngoc Duy; Bellet, Daniel
Abstract: Transparent electrodes (TEs) are pivotal components in many modern devices such as solar cells, light‐emitting diodes, touch screens, wearable electronic devices, smart windows, and transparent heaters. Recently, the high demand for flexibility and low cost in TEs requires a new class of transparent conductive materials (TCMs), serving as substitutes for the conventional indium tin oxide (ITO). So far, ITO has been the most used TCM despite its brittleness and high cost. Among the different emerging alternative materials to ITO, metallic nanomaterials have received much interest due to their remarkable optical‐electrical properties, low cost, ease of manufacturing, flexibility, and widespread applicability. These involve metal grids, thin oxide/metal/oxide multilayers, metal nanowire percolating networks, or nanocomposites based on metallic nanostructures. In this review, a comparison between TCMs based on metallic nanomaterials and other TCM technologies is discussed. Next, the different types of metal‐based TCMs developed so far and the fabrication technologies used are presented. Then, the challenges that these TCMs face toward integration in functional devices are discussed. Finally, the various fields in which metal‐based TCMs have been successfully applied, as well as emerging and potential applications, are summarized. Abstract : Recent progress and remaining challenges on metallic nanostructure‐based transparent electrodes (TEs), including oxide/metal/oxide multilayers, metal grids, metal nanowire/nanofiber/nanotrough percolating networks, metal meshes based on cracked templated, dealloyed ultrathin metallic films and some important nanocomposites, are reviewed and discussed. The various fields in which metal‐based TEs have been successfully applied as well as emerging and potential applications are summarized.